ARTHRALGIA IN A YOUNG PATIENT: PRESENTATION OF LOFGREN SYNDROME - Ali, Junaid; Zeb, Junaid; Shah, Maleeha; Jamil, Shahid (Journal of Ayub Medical College Abbottabad, 2022)
1Department of Medicine, 2Department of Orthopedics, Khyber Teaching Hospital, Peshawar-Pakistan Lofgren syndrome an acute form of sarcoidosis constitutes erythema nodosum, bilateral hilar adenopathy and arthralgia or arthritis. Here we present a case of a 28 years old young male patient who is a shopkeeper and farmer by profession admitted to inpatient department with chief complaints of bilateral painful nodules on his shins, low grade fever and pain multiple joints on both sides of the body. Suspicion of the Lofgren syndrome was made upon initial evaluation and patient was admitted to inpatient care facility for necessary comprehensive workup. Radiological findings were consistent with bilateral hilar lymphadenopathy and patient was diagnosed with Lofgren syndrome. Patient was started on non-steroidal inflammatory drugs (NSAIDs) with close observation for improvement in response to treatment. After one weak of treatment in hospital, patient was discharged home when his symptoms started to resolve.